Pendampingan Pemasangan U-Dicth untuk Saluran Drainase Ruas Jalan Semarang-Godong Provinsi Jawa Tengah - Cahyono, Dhamang Budi; Triyono, AR Hanung; Widiatmoko, Kukuh Wisnuaji; Billahi, Bagus Acung; Mahmud, Faizal (Faculty of Engineering, Universitas Semarang, 2026)
The Community Service Program (PkM) conducted by the Faculty of Engineering, Universitas Semarang, in collaboration with PT. Valentara Sarana Raya and the community of Godong Village aimed to improve the drainage function along the Semarang–Godong road and enhance the technical skills of construction workers through training and mentoring in the installation of precast u-ditch drains. The program was carried out from September to December 2025, with the main field activity on October 24, 2025. A total of 15 workers participated in the training, showing an increase in average scores from 56.7 to 88.5, or a 56.1% improvement, particularly in technical installation and occupational safety practices. Technically, a 120-meter u-ditch channel was successfully installed in compliance with the Ministry of Public Works Regulation No.14/PRT/M/2018, reducing flooding by up to 90%. The activity also established the “Godong Drainage Task Force (POKJA Drainase Godong)” to ensure continuous maintenance. The program outputs include a publication in the journal, online media coverage, a documentation video on the LPPM USM YouTube channel, and a registered intellectual property poster titled “Technical Assistance for U-ditch Installation.” Overall, this PkM successfully improved drainage infrastructure, enhanced the competencies of local workers, and strengthened community participation, serving as a replicable model of sustainable, community-based implementation of the tri dharma of higher education.